STRATEGY TO INCREASE EMPLOYEE PRODUCTIVITY AT PT PERKEBUNAN NUSANTARA XIV (TAKALAR SUGAR FACTORY) - Rizal, Samsul; Iqbal, Muhammad; Handayani, Desi (Jurnal Ekonomi Balance, 2019)
This study aims to determine how the Strategy for Increasing Employee Productivity at PT Perkebunan Nusantara XIV (Takalar Sugar Factory). This research is descriptive qualitative, by trying to describe the results of the research as it is. Data collection techniques using observation, interviews. The data obtained is then processed in the form of words or text which is then poured in a descriptive form. The results of the study explained that there are three strategies used at PT Perkebunan Nusantara XIV (Takalar Sugar Factory) in an effort to increase employee productivity, namely: by providing training, every year there is an assessment of employee performance and improving effective communication. with the training it is able to produce a positive impact, but its application is still less than perfection because the application of the strategies used has not been done regularly and is well structured. But the leadership is expected to increase training and establish more active communication to the head of the department and employees so that the company is more improved and developed.